Evaluation of two blood microsampling approaches for drug discovery PK studies in rats. (September 2015) - Luo, Yongyi; Korfmacher, Walter; Ho, Stacy; Shen, Liduo; Wang, Jie; Wu, Zhongtao; Guo, Yang; Snow, Gregory; O'Shea, Thomas
Background: Serial sampling in discovery rat PK studies could be performed via capillary microsampling (CMS) of blood or by using the Mitra™ device to collect dried blood samples.Results: Blood CMS results were compared with Mitra sampling results for four test compounds dosed in rat PK studies. The PK profiles obtained from CMS sampling were found to be very similar to those obtained from the Mitra sampling. For 15-µl blood CMS samples, freezing before the dilution step was found to be acceptable.Conclusion: Blood CMS using 15-µl glass capillary microsamples works well for serial blood sampling in rat PK studies. The Mitra microsampling device provides an alternative method for collecting 10 µl of blood as a dried blood sample.